Analisis Pengaruh Pelatihan dan Pengembangan Karyawan terhadap Produktivitas Kerja di Perusahaan Sinar Maju Indonesia - Dedi Muliadi (Jurnal Ekonomi Manajemen Akuntansi, 2025)
This study analyzes the influence of Employee Training and Employee Development on Work Productivity at Sinar Maju Indonesia Company. Using a quantitative approach with a survey design, data was collected through a questionnaire distributed to 30 employees. Data analysis using simple linear regression showed a regression coefficient of 0.75. These results indicate that there is a positive and significant influence between Employee Training and Employee Development on Work Productivity at Sinar Maju Indonesia Company. An increase in training intensity is associated with an increase in work productivity. These findings support the importance of investing in Employee Training and Employee Development to improve performance and efficiency in companies. Therefore, it is recommended that the management of Sinar Maju Indonesia Company continue and even improve its Employee Training and Employee Development programs to maximize their potential and achieve the company's goals. This research contributes to the development of human resources in the industrial sector and can be a reference for future research.